EVALUASI PENGELOLAAN DAN PROBLEMATIKA LAPORAN KEUANGAN MASJID DI KABUPATEN PONOROGO BERDASARKAN PSAK 45 - Sri Hartono; Titi Rapini; Rizki Listyono Putro (Jurnal Ilmiah Akuntansi Indonesia, 2020)
Mosque is a non-profit organization arranged by Indonesian Constitution No. 17 of 2013 about Community Organization. Mosque manages a lot of social activities and collects fund in a large amount from congregation, so that the fund management is have to arranged professionally in order to create a transparent and accountable financial report. The Financial report of mosque is guided by PSAK No. 45. This study has three aims; the first is to digging information about the management of financial report, media of publications, mosque’s bank account, the source of revenue of mosque’s fund and the audit of financial report; the second aim is to digging information about the problems on drafting the financial report based on applicable  financial standard’ and the third aim is to evaluate the practice of drafting mosque’s financial report according to the facts and drafting non profit’s financial report based on PSAK 45. The sample of this study is 25 mosques in Ponorogo by the random sampling method. This study is a descriptive qualitative with the primary and secondary data use the observation, interview and documentation. The result of this study shows that the majority mosques in Ponorogo have compiled the financial report and the type of financial report is an expense and income report only. The awareness of importance of financial publication is already reflected by the various ways of delivery, namely written on the blackboard, announcement board, photocopies distributed by congregants and announced every Friday prayer. Judging from the ownership of the mosque account, it is still combined into one personal account of the mosque management. The mosque's acceptance comes from donations, alms and waqf via cash, most of them still have not implemented online transactions. No mosque has yet been audited for financial reports. Financial management has not implemented recording based on PSAK 45, due to several factors. It needs to be evaluated through FGD (focus group discussion) and carried out regularly to reconstruct the financial reports of mosques in Ponorogo Regency based on article 45.